2022
DOI: 10.1186/s40795-022-00511-0
|View full text |Cite
|
Sign up to set email alerts
|

Addressing child undernutrition in Tanzania with the ASTUTE program

Abstract: Background Optimal infant and young child feeding practices (IYCFP) reduce childhood stunting and are associated with additional health benefits. In Tanzania, IYCFP are far from optimal where 32% of children under the age of 5 years are stunted. The purpose of this study was to examine whether behavior change communication focused on reducing child undernutrition was associated with improved IYCFP in Tanzania. Methods A cross-sectional survey was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…rendering any additional significant improvements in the population statistically challenging. For example, in their analysis of endline-only ASTUTE data, Beckstead et al [9] found significant associations between exposure to SBCC radio programming and a variety of IYCF practices as well as significant associations between SBCC television programming and IYCF knowledge. Significant findings between SBCC exposure and enline data from Beckstead et al may be helpful in gauging the impact of SBCC programming on indicators that are high at each of the three data collection periods in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…rendering any additional significant improvements in the population statistically challenging. For example, in their analysis of endline-only ASTUTE data, Beckstead et al [9] found significant associations between exposure to SBCC radio programming and a variety of IYCF practices as well as significant associations between SBCC television programming and IYCF knowledge. Significant findings between SBCC exposure and enline data from Beckstead et al may be helpful in gauging the impact of SBCC programming on indicators that are high at each of the three data collection periods in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…IMA partnered with Development Media International (DMI)-its partner in the development and implementation of radio and TV spots-to design and conduct baseline, midline, and endline surveys to inform program direction and to assess impact during, in the middle, and at the end of the program. Numerous studies exploring the associations of key health outcomes and exposure to core program elements and indicators at either baseline, midline, or endline have been published previously [9][10][11][12][13][14][15][16][17][18]. Associations between knowledge of key health-promoting behaviors included in SBCC programming and stunting prevention have been significant [10,13,15].…”
Section: Introductionmentioning
confidence: 99%